Composite Baraitot in the Tosefta in Light of Their Parallels in the Palestinian Talmud - Shmidman, Shira (Zutot, 2024)
In this article I present three cases in the first chapter of Yevamot where a baraita in the Tosefta is cited as multiple smaller sources in the Yerushalmi. I demonstrate that in all three cases, the Palestinian Talmud preserved the more original form of the baraitot, while the Tosefta contains a later, edited form of the tannaitic material in which multiple baraitot are combined into one. Furthermore, I consider the implications of this phenomenon for understanding the nature of baraitot in both the Palestinian Talmud and the Tosefta, as well as how these baraitot developed into their final form.